2024
DOI: 10.3389/fpsyg.2024.1330971
|View full text |Cite
|
Sign up to set email alerts
|

Empowering motivation: the journey of wheelchair basketball athletes to overcome constraints

Halil Sarol

Abstract: IntroductionThe aim of this phenomenological study is to determine the motivational factors in the participation of wheelchair basketball players in sports according to Self-Determination Theory.MethodsThe study group of the research was determined by the criterion sampling method, which is one of the purposeful sampling methods. Accordingly, thirteen (13) wheelchair athletes constituted the study group. In the research, a personal information form and a semi-structured interview form were prepared as data col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Moreover, personal barriers such as economic hardships, lack of personal transportation, the psychological repercussions of disability, and challenges in social adaptation also pose significant barriers to sports participation. In line with the findings of this study, Sarol (2024) similarly reported that structural issues such as transportation, equipment, accommodation, and financial constraints faced by clubs were primary barriers for participants. Additionally, it is noted that the use of prosthetics, susceptibility to infectious diseases associated with disability, and difficulties in limb mobility further hinder individuals' participation in sports.…”
Section: Obstacles To Sports Participationsupporting
confidence: 86%
See 4 more Smart Citations
“…Moreover, personal barriers such as economic hardships, lack of personal transportation, the psychological repercussions of disability, and challenges in social adaptation also pose significant barriers to sports participation. In line with the findings of this study, Sarol (2024) similarly reported that structural issues such as transportation, equipment, accommodation, and financial constraints faced by clubs were primary barriers for participants. Additionally, it is noted that the use of prosthetics, susceptibility to infectious diseases associated with disability, and difficulties in limb mobility further hinder individuals' participation in sports.…”
Section: Obstacles To Sports Participationsupporting
confidence: 86%
“…Additionally, the study concludes that challenges associated with using prosthetics, acquiring disabilities later in life, and health issues stemming from disability significantly impact sports participation, findings supported by existing literature (Jaarsma et al, 2014a;Jaarsma et al, 2014b;Sarol, 2024). Furthermore, is highlighted that participants face negative attitudes from their supervisors due to their employment status and that comparing the performance of disabled individuals with other employees has adverse consequences.…”
Section: Obstacles To Sports Participationsupporting
confidence: 65%
See 3 more Smart Citations